2016
DOI: 10.1152/ajplung.00263.2015
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylation contributes to low extracellular superoxide dismutase expression in human idiopathic pulmonary arterial hypertension

Abstract: Epigenetic mechanisms, including DNA methylation and histone acetylation, regulate gene expression in idiopathic pulmonary arterial hypertension (IPAH). These mechanisms can modulate expression of extracellular superoxide dismutase (SOD3 or EC-SOD), a key vascular antioxidant enzyme, and loss of vascular SOD3 worsens outcomes in animal models of pulmonary arterial hypertension. We hypothesized that SOD3 gene expression is decreased in patients with IPAH due to aberrant DNA methylation and/or histone deacetylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 58 publications
1
33
2
Order By: Relevance
“…While overexpression of EC-SOD attenuated (172), and total body loss of EC-SOD accentuated (271), hypoxic PH, the results from conditional EC-SOD deletion suggest that EC-SOD bound to SMC may be a key regulator of oxidant-induced injury in the CH model of PH. These findings are consistent with recent work demonstrating reduction in EC-SOD expression in lung tissue and PASMCs from PAH patients mediated by histone deacetylation (173).…”
Section: Pathways and Targetssupporting
confidence: 93%
“…While overexpression of EC-SOD attenuated (172), and total body loss of EC-SOD accentuated (271), hypoxic PH, the results from conditional EC-SOD deletion suggest that EC-SOD bound to SMC may be a key regulator of oxidant-induced injury in the CH model of PH. These findings are consistent with recent work demonstrating reduction in EC-SOD expression in lung tissue and PASMCs from PAH patients mediated by histone deacetylation (173).…”
Section: Pathways and Targetssupporting
confidence: 93%
“…Further experimentation would help clarify the findings of Zhao et al, who identified the increased expression of HDAC1/4/5 in lungs from human idiopathic PAH, but only focused on the role of HDAC1/5 in remodeled pulmonary vessels . Nozik‐Grayck and colleagues found that HDAC3 induced the suppression of superoxide dismutase (ie, superoxide dismutase 3) in PASMCs and suggested that the HDAC pan‐inhibitor Trichostatin A (TSA) may protect against idiopathic PAH, in part, by blocking HDAC3 activity and increasing PASMC superoxide dismutase 3 expression …”
Section: Discussionmentioning
confidence: 99%
“…63 Nozik-Grayck and colleagues found that HDAC3 induced the suppression of superoxide dismutase (ie, superoxide dismutase 3) in PASMCs and suggested that the HDAC pan-inhibitor Trichostatin A (TSA) may protect against idiopathic PAH, in part, by blocking HDAC3 activity and increasing PASMC superoxide dismutase 3 expression. 64 To elucidate the regulatory mechanisms of the miR-1281/ HDAC4 pathway, 2 possible actions of HDAC4 were considered: it may be globally influencing the PASMC transcriptome by altering the acetylation status of histone(s), or it may be specifically interacting with related commanding transcription factors. The data from our study support the latter case.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitors against histone acetyltransferases (HATs), such as GCN5, p300, and PCAF, prevented EcSOD increases in a stimulated monocytic leukemia cell line, THP-1 [170]. Additionally, several studies have demonstrated increased EcSOD expression with histone deacetylase (HDAC) inhibitors [116 170 171 179 180]. Specifically, inhibition or knockdown of HDAC3 led to increased EcSOD expression in pulmonary artery smooth muscle cells [179].…”
Section: Deregulation Of Ecsod In Cancersmentioning
confidence: 99%
“…Additionally, several studies have demonstrated increased EcSOD expression with histone deacetylase (HDAC) inhibitors [116 170 171 179 180]. Specifically, inhibition or knockdown of HDAC3 led to increased EcSOD expression in pulmonary artery smooth muscle cells [179]. HDAC3 is up-regulated in many solid cancers, such as lung, breast, pancreatic, liver, and colon, indicating another potential mechanism of EcSOD silencing in cancer [181185].…”
Section: Deregulation Of Ecsod In Cancersmentioning
confidence: 99%